Exploring the Relationship Between Social Identity Factors and Academic Performance: Insights from Nigerian Colleges of Education (Jurnal Penelitian dan Pengkajian Ilmu Pendidikan: e-Saintika, 2024)
This study examines the influence of social identity factors—age, gender, and socioeconomic status—on the academic performance of Social Studies students in Colleges of Education in Delta State, Nigeria. Using a correlational design, data were collected from a purposive sample of 80 students, drawn from a population of 253 across two institutions. The Social Identity Group and Academic Performance Test (SIGAPT) and an academic test were used as instruments. Data analysis was conducted using the coefficient of determination for research questions and linear regression for hypothesis testing at a 0.05 significance level, with SPSS software. The findings revealed that age significantly influences academic performance (R2=0.166), accounting for 16.6% of the variance. This underscores the importance of cognitive development and maturity associated with age in educational success. In contrast, gender and socioeconomic status showed no significant relationship with academic performance, suggesting that institutional equality measures may mitigate traditional disparities. This study contributes uniquely to the field by addressing the underexplored domain of higher education, particularly in Colleges of Education, which are critical for teacher preparation. The findings highlight the need for age-sensitive educational interventions and sustained equity-focused policies to optimize academic outcomes. These insights are valuable for educators and policymakers in fostering inclusive and effective learning environments.